Perceptions of Socially Responsible Activities and Attitudes: A Comparison of Business School Deans and Corporate Chief Executives - Ford, Robert; McLaughlin, Frank (Academy of Management Journal, 1984)
The article discusses a study which compared the attitudes of executives and business school deans in relation to corporate social responsibility. The study sought to determine whether or not business leaders and business educators are in agreement as to what practices are evidence of social responsible behavior, how intensely these activities are being supported by business leaders, and what arguments for and against the acceptance of corporate social responsibility have merit. The study concludes that both deans and chief executive officers (CEO) recognize very similar priorities for socially responsible activities.